1991
DOI: 10.1182/blood.v77.10.2190.2190
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the binding domains on platelet glycoproteins Ib-IX and IIb/IIIa complexes for the quinine/quinidine-dependent antibodies

Abstract: Sera of 12 patients with quinine/quinidine-induced thrombocytopenia showed drug-dependent antibody binding to glycoprotein (GP) Ib-IX complex. The reaction with GPIb-IX complex of 11 of these 12 sera was strongly inhibited by the complex-specific monoclonal antibodies (MoAbs) AK1 and SZ1. The exception was a quinine-induced serum designated BU. The reaction of the six quinidine-induced sera was also partially blocked by an anti-GPIX MoAb, FMC25. Only 3 of the 12 patient sera showed drug-dependent antibody bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…These results suggest that the binding epitope of the antibody is identical or is located very close to the domains recognized by the mAbs SZ1 and BL-H6, as the antibody cross-blocked the binding of both mAbs to GPIX. This notion is further supported by two recent studies showing that the binding of SZ1 to GPIb/IX complex was also blocked by six different quinidinedependent antibodies (Chong et al, 1991) and a ranitidinedependent antibody (Gentilini et al, 1998).…”
Section: Discussionsupporting
confidence: 63%
“…These results suggest that the binding epitope of the antibody is identical or is located very close to the domains recognized by the mAbs SZ1 and BL-H6, as the antibody cross-blocked the binding of both mAbs to GPIX. This notion is further supported by two recent studies showing that the binding of SZ1 to GPIb/IX complex was also blocked by six different quinidinedependent antibodies (Chong et al, 1991) and a ranitidinedependent antibody (Gentilini et al, 1998).…”
Section: Discussionsupporting
confidence: 63%
“…Most DDAbs specific for PLTs bind to epitopes on the GPIIb/IIIa and/or GPIb/IX complexes. 4,7,10,11 However, the binding pattern of DDAbs on either GP is heterogeneous. Whereas some quinidine-dependent DDAbs against GPIIb/IIIa required the intact complex for binding, others were able to precipitate dissociated GPIIIa.…”
Section: Discussionmentioning
confidence: 99%
“…11 Inhibition studies with panels of MoAbs against the respective GP revealed evidence for various DDAb epitopes on GPIIb/ IIIa and GPIb/IX. 4,11 Recently, Peterson et al 32 demonstrated that substitution of the amino acids 50, 62, and 66 of GPIIIa abolished the binding of a subgroup of GPIIIaspecific quinidine DDAbs. GPIIb/IIIa-specificity of ceftriaxone DDAbs in Patient 1 could be demonstrated by MAIPA assay and with stable CHO transfectants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although at least 100 drugs have been implicated in DITP, convincing data for a causal relationship between medications and immunemediated thrombocytopenia exists for a more selective group of drugs, 19 which include quinine and quinidine (cinchona alkaloid derivatives), penicillin, vancomycin, abciximab, ranitidine, sulfonamides, gold salts, thiazide diuretics (which can also mediate megakaryocyte suppression), and antirheumatic and oral antidiabetic drugs. [19][20][21][22][23][24] Rapid development of thrombocytopenia typically manifests 7 days after starting a new drug or within 2 to 3 days of reexposure.…”
Section: Discussionmentioning
confidence: 99%